Design of a new chaotic system by a non-smooth controller and its application - He, Jianbin; Zhao, Kun; Wang, Shiya (Zielona Góra: Uniwersytet Zielonogórski)
Chaos theory constitutes a fundamental discipline within nonlinear science. Chaotic systems, leveraging their sensitive dependence on initial conditions, have found extensive applications in information security. While numerous chaotic systems have been developed via continuous control methodologies in recent years, the design of such systems under non-smooth control regimes remains challenging due to the lack of systematic theoretical frameworks.
Keywords: chaotic system; non-smooth control; pseudo-random sequence; image encryption